KEKUASAAN DAN WEWENANG POLITIK DALAM TATA KELOLA PEMERINTAHAN MODERN - Salma Sausan Hakim; Saeful Mujab (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Power and political authority are key elements in modern government, determining the direction of public policy and the stability of the political system. Power is understood as the ability to influence decisions and behaviour within the political realm, while authority refers to the legitimacy that accompanies the use of power based on laws and norms. This study aims to analyse the relationship between power and authority, identify the causes of power abuse, and examine the mechanisms of governance oversight. The study was conducted using a qualitative approach through a literature review of relevant books and academic journals. The results of the analysis show that imbalances between power and authority can lead to abuse of power, reduced accountability, and decreased public trust in the government. Faktor-faktor seperti lemahnya pengawasan, rendahnya integritas aparatur, dan dominasi kepentingan politik berkontribusi terhadap penyimpangan ini. The implementation of good governance principles such as transparency, accountability, and public participation is necessary to maintain balance in the use of power. Strengthening the oversight mechanism and consistent law enforcement is expected to create a more effective, fair and people-oriented governance system.